An endogenous promoter LpSUT2 discovered in duckweed: a promising transgenic tool for plants - Wei, Cuicui; Hu, Zhubin; Wang, Songhu; Tan, Xiao; Jin, Yanling; Yi, Zhuolin; He, Kaize; Zhao, Leyi; Chu, Ziyue; Fang, Yang; Chen, Shuang; Liu, Penghui; et al. (Frontiers in Plant Science, 2024)
Promoters are one of the most critical elements in regulating gene expression. They are considered essential biotechnological tools for heterologous protein production. The one most widely used in plants is the 35S promoter from cauliflower mosaic virus. However, our study for the first time discovered the 35S promoter reduced the expression of exogenous proteins under increased antibiotic stress. We discovered an endogenous strong promoter from duckweed named LpSUT2 that keeps higher initiation activity under antibiotic stress. Stable transformation in duckweed showed that the gene expression of eGFP in the LpSUT2:eGFP was 1.76 times that of the 35S:eGFP at 100 mg.L -1 G418 and 6.18 times at 500 mg.L -1 G418. Notably, with the increase of G418 concentration, the gene expression and the fluorescence signal of eGFP in the 35S:eGFP were weakened, while the LpSUT2:eGFP only changed slightly. This is because, under high antibiotic stress, the 35S promoter was methylated, leading to the gene silencing of the eGFP gene. Meanwhile, the LpSUT2 promoter was not methylated and maintained high activity. This is a previously unknown mechanism that provides us with new insights into screening more stable promoters that are less affected by environmental stress. These outcomes suggest that the LpSUT2 promoter has a high capacity to initiate the expression of exogenous proteins. In conclusion, our study provides a promoter tool with potential application for plant genetic engineering and also provides new insights into screening promoters.